2002
DOI: 10.1105/tpc.005579
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Effects of Cytosolic Free Calcium Increases in Response to Elicitors in Nicotiana plumbaginifolia Cells

Abstract: Cell suspensions obtained from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
315
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(338 citation statements)
references
References 98 publications
19
315
2
2
Order By: Relevance
“…Indeed, CBEL triggered a bimodal increase in [Ca 2þ ] cyt when administered to aequorin-transformed BY-2 tobacco cells and not to tobacco protoplasts. Induction of biphasic increases of [Ca 2þ ] cyt have been reported for tobacco cells treated with cryptogein and oligouronide elicitors (Lecourieux et al, 2002) and Pep-13-treated parsley (Petroselinum crispum) cells (Blume et al, 2000). In these studies, the induced calcium fluxes were shown to be tightly correlated to elicitor perception and were required for defense activation.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, CBEL triggered a bimodal increase in [Ca 2þ ] cyt when administered to aequorin-transformed BY-2 tobacco cells and not to tobacco protoplasts. Induction of biphasic increases of [Ca 2þ ] cyt have been reported for tobacco cells treated with cryptogein and oligouronide elicitors (Lecourieux et al, 2002) and Pep-13-treated parsley (Petroselinum crispum) cells (Blume et al, 2000). In these studies, the induced calcium fluxes were shown to be tightly correlated to elicitor perception and were required for defense activation.…”
Section: Discussionmentioning
confidence: 79%
“…Plant GLRs were confirmed recently to be NSCC (Price et al, 2012;Forde, 2014). Therefore, activated by Glu, GLR may mediate stress-induced Ca 2+ uptake, with a consequent rise in cytosolic Ca 2+ , that in turn can activate the plasma membrane NADPH oxidase (Lecourieux et al, 2002), leading to elevated H 2 O 2 levels and a consequent formation of OH $ (as discussed above), leading to a massive K + efflux via OH $ -activated outward-rectified (GORK) K + channels (Demidchik et al, 2010). Thus, the strong increase in Glu levels found in the root apex (Table I) may be an additional factor exacerbating a stress-induced decrease in the cytosolic K + pool in this zone, leading to the activation of caspase-like enzymes and, finally, programmed cell death (Fig.…”
Section: Changes In Primary Metabolism Exacerbate Differential K + Rementioning
confidence: 94%
“…Ca 2+ has been proposed as important signaling molecule playing role as an intracellular secondary messenger in plants under various abiotic stresses, but few studies have explored its importance under biotic stress also (Blume et al 2000;Lecourieux et al 2002). Cyclic nucleotide-gated channels (CNGCs)-Ca 2+ influx has been studied in Arabidopsis, which showed that this influx is mediated by CNGC 2, CNGC 4, CNGC 11 and CNGC 12 after elicitor perception (Urquhart et al 2011).…”
Section: Calcium Signalingmentioning
confidence: 99%